Temporalités dans la recherche biomédicale : la science au travail saisie par le temps - Philippe Brunet (La Nouvelle Revue du Travail)
The article seeks to understand and analyse the growing importance of time in scientific work. Science is usually seen as an activity with an intrinsic rhythm that seems to escape time. Based on the phenomenon of contextualisation, however, we will show that time has become a way of measuring work processes. Using data from a biomedical research laboratory study, the analysis identifies three time scales: an intrinsic professional temporality; an extrinsic social temporality; and a hybrid managerial temporality. It is at the interface between these three temporalities that tensions affect laboratory work processes. The main issue at stake is scientists’ professional autonomy. In the case being analysed here, managerial temporality appears as something that measures time in science and protects the autonomy thereof.